2009
DOI: 10.1175/2009jcli3049.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Global Hurricane Climatology, Interannual Variability, and Response to Global Warming Using a 50-km Resolution GCM

Abstract: A global atmospheric model with roughly 50-km horizontal grid spacing is used to simulate the interannual variability of tropical cyclones using observed sea surface temperatures (SSTs) as the lower boundary condition. The model’s convective parameterization is based on a closure for shallow convection, with much of the deep convection allowed to occur on resolved scales. Four realizations of the period 1981–2005 are generated. The correlation of yearly Atlantic hurricane counts with observations is greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
727
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 603 publications
(772 citation statements)
references
References 48 publications
(60 reference statements)
42
727
2
1
Order By: Relevance
“…This analysis draws a parallel with tropical cyclone studies, in which the densities and directions of their tracks have been analyzed in the world's oceans [Zhao et al, 2009].…”
Section: Resultsmentioning
confidence: 99%
“…This analysis draws a parallel with tropical cyclone studies, in which the densities and directions of their tracks have been analyzed in the world's oceans [Zhao et al, 2009].…”
Section: Resultsmentioning
confidence: 99%
“…The ocean component of the intensity model requires ocean mixed layer depth and sub mixed layer thermal stratification; in the simulations described here, we use present-day climatology for both these quantities. Thus, the effect of global warming on the thermal (11,19) and the regional downscaling model of Knutson et al (20), which was also driven by NCAR/NCEP reanalysis data. The technique captures well the observed spatial and seasonal variability of tropical cyclones around the globe, as well as the effects of such climate phenomena as El Nino Southern Oscillation (ENSO) and the Atlantic Meridional Mode (9).…”
Section: Technique and Modelsmentioning
confidence: 90%
“…A clear advantage of direct simulation is that it requires no additional assumptions or model applications (other than the detection algorithm). An important limitation of this approach is that it severely underresolves tropical cyclones, resulting in a substantial truncation of the intensity spectrum of simulated storms, even at 50-km grid spacing (11), and usually produces fewer events than observed (12).…”
mentioning
confidence: 99%
“…Changes in the intensity distribution of hurricanes occurring in concert with changes in storm frequency could cause the frequency of storm deposits in sites with different flooding susceptibilities to diverge. Numerical modeling of late 21 st century hurricane climatology has suggested that declines in overall Atlantic hurricane frequency could occur simultaneously with a broadening of the intensity distribution of hurricanes leading to fewer but more intense storms , Gualdi et al 2008, Knutson et al 2008, Zhao et al 2009, Bender et al 2010). However, recent warming and increased hurricane frequency in the Atlantic has purportedly been accompanied by a disproportionate increase in the occurrence of intense hurricanes (Emanuel 2005, Webster et al 2005, Hoyos et al 2006.…”
Section: Comparisons With Other Paleohurricane Recordsmentioning
confidence: 99%